2007
DOI: 10.1177/089686080702700502
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Plasma Total Homocysteine in Patients with End-Stage Renal Disease

Abstract: Elevated plasma total homocysteine (tHcy) is a risk factor for cardiovascular disease; however, in light of several recent randomized trials, the issue of causality has been cast into doubt. Patients with end-stage renal disease are particularly interesting as they consistently have elevated tHcy and their leading causes of morbidity and mortality are related to cardiovascular disease. In the present article, we review the early evidence for the homocysteine theory of atherosclerosis, homocysteine metabolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 108 publications
1
4
0
1
Order By: Relevance
“…Induction of oxidative stress and the promotion of in ammation and thrombosis are mechanisms by which the increased Hcy may be involved in advanced athero-sclerosis [35]. Our results indicated that dialysis can remove Hcy, similar to the results reported in a review article by Urquhart et al [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Induction of oxidative stress and the promotion of in ammation and thrombosis are mechanisms by which the increased Hcy may be involved in advanced athero-sclerosis [35]. Our results indicated that dialysis can remove Hcy, similar to the results reported in a review article by Urquhart et al [17].…”
Section: Discussionsupporting
confidence: 90%
“…ese homocysteinylated proteins could induce autoimmune responses and play a role in pathogenesis of atherosclerosis [16]. Several studies have shown that there are elevated Hcy levels in patients with ESRD [17]; however, there is no the proven evidence for increased Hcy in renal disease. Perhaps, performing of the direct experiments on homocysteinemetabolizing enzymes could be helpful in revealing the cause of hyperhomocysteinemia in renal disease [17].…”
mentioning
confidence: 99%
“…Indeed more than 90% of patients with advanced CKD have hyperhomocysteinaemia. Prospective observational studies show a greater risk of coronary artery disease in the presence of elevated homocysteine levels (161) and it is an independent risk factor for the development of cardiovascular disease (162). Mechanisms include inducing dysfunction of the vascular endothelium, (163) increasing proliferation of VSMC (164) and increasing oxidative stress (165).…”
Section: Homocysteine and Hyperuricaemiamentioning
confidence: 99%
“…Elevated homocysteine has been associated with worsening cardiovascular outcomes in a number of observational studies [ 54 ], and has been a target of study in CKD. However, vitamin therapy to lower homocysteine has been unhelpful in patients with advanced CKD [ 55 , 56 ] and harmful in patients with diabetes and more moderate CKD [ 57 ].…”
Section: Management Of Chronic Reno-cardiac Syndrome (Type 4)mentioning
confidence: 99%